ISFET Fabrication and Characterization for Hydrogen Peroxide sensing - Duarte, Pedro H.; Rangel, Ricardo C.; Ramos, Daniel A.; Yojo, Leonardo S.; Mori, Carlos A. B.; Sasaki, Katia R. A. [UNESP]; Agopian, Paula G. D. [UNESP]; Martino, Joao A. (My University, 2023)
This work presents the Ion-Sensitive Field Effect Transistor (ISFET) fabrication and electrical characterization for hydrogen peroxide sensing. Two configurations were set up to evaluate the devices sensitivity to the concentration of the solution. First, measurements with one electrode in the sample solution (contained over the gate area) were performed, but the results may not be directly related to the characteristics of the solution, due to the prevalence of secondary effects. The second method, using two electrodes in the sample solution, shows a higher sensitivity at increasing hydrogen peroxide concentrations, in smallest intervals when compared to measurements with one electrode.
Keywords: Biosensor; Hydrogen Peroxide sensing; ISFET